Using competing traits to select dual-purpose sweet potato in native germplasm - León-Velarde, C.U. (2001)
Eighteen accessions of sweetpotato (Ipomea batata L.) were selected using the ratio of root/forage dry-matter production (R/F) and classified into four groups: (1) forage, (2) low dual-purpose, (3) high dual-purpose, and (4) low forage-high root production. Roots and vines produced between 120 and 150 days on plots of 10 square meters were evaluated over two years and analyzed in a fixed linear covariance model, including group, accession (group), and days as covariables. There was a significant difference among groups (P < 0.01) for total forage and root dry matter, total commercial roots, and root to forage dry matter. Significant differences of accessions within groups on total forage dry matter and commercial roots indicate that there is enough within-group variability among the accessions to allow a process of selection. The least-squares means for dry-matter forage production ranged from 6.07 ± 0.27 kg/10m2 for group 1 to 4.43 ± 0.38 kg/10 m2 for group 4. Total root production dry matter (DM) ranged from 2.04 ± 0.54 kg/10 m2 for group 1 to 8.22 ± 0.50 kg/10 m2 for group 4. The total commercial root produced was 2.99 ± 0.60 kg DM/10 m2 for group 2 and 3.32 ± 0.55 kg/10 m2 for group 3. This represents 132% more root production than group 1 and almost 36% less than group 4. The average weight of commercial root ranged from about 144 g to 259 g, with a significant difference between groups. The results show that a number of accessions have potential as dual-purpose sweetpotatoes. These are DLP-3548, DLP2481, ARB265, and ARB-158, defined as forage in group 1; DLP-3525 and DLP-2462, defined as low dual-purpose; and ARB-394 and DLP-275A, defined as high dual-purpose.